Improving the adsorption performance of non-polar benzene vapor by using lignin-based activated carbon - Isinkaralar, Kaan (Springer Science and Business Media LLC, 2023)
Both indoor and outdoor contamination continually contain benzene vapor. It has primary concerns about long-term health risks to the living environment. Benzene is a crucial airborne pollutant in the environment due to its apparent acute toxicity, high volatility, and poor degradability. It is especially urgent to restrain benzene emissions due to the persistent concentration increase and stringent processes. Benzene adsorption is a highly efficient mechanism with low cost, low energy consumption, and a simple process. In this study, biomass-derived porous carbon materials (TCACs) were synthesized by pyrolysis activation combined with H3PO4, HNO3, and HCl. TCAC44 has the best activation conclusion, showing that surface area and pore volume were 1107 m2/g and 0.58 cm3/g treated with H3PO4 and so was chosen for subsequent benzene adsorption/desorption tests. The adsorption capacities of benzene for TCAC44 were increased from 58 mg/g for 35 °C + 95% RH to 121 mg/g for 25 °C + 15% RH and presented a higher adsorption capacity of benzene than TCAC101 and TCAC133. Otherwise, well recyclability of TCAC44 was revealed as the benzene adsorption capacity reductions were 22.49% after five adsorption-desorption cycles. Furthermore, the present study established the property-application relationships to promote and encourage future research on the newly synthesized innovative TCAC44 for benzene removal.
Keywords: Volatile Organic Compounds; Charcoal; Benzene; Adsorption; Gases; Lignin; 13. Climate action; 7. Clean energy